In vitro antioxidant, antifungal and cytotoxic activity of methanolic extract of Calligonum polygonoides (Bangladesh Journal of Pharmacology, 2015)
Present study is aimed at the pharmacological characterization of methanol extract of Calligonum polygonoides from District Bannu. Dried plant was grounded and extracted with methanol to prepare methanol crud extract. In vitro biological assays were conducted using this methanolic extract according to standard protocol. Cytotoxic activity of plant methanolic extract against brine shrimps while antifungal activity was also measured.  Eighty percent death rate of brine shrimp was observed at 1,000 ?g/mL of plant extract. 70 ± 0.0% growth inhibition of Aspergillus niger was measured during the present study. Significant scavenging results were observed during scavenging of free radicles viz; 78.1% against DPPH, 83.1% to ABTS and 36% against superoxide at 500 ?g/mL were obtained. The results obtained in this study indicate that C. polygonoides possess significant antioxidant, antifungal and cytotoxic bioactive compounds.